2013
DOI: 10.3109/0886022x.2013.766573
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Peritoneal and Hemodialysis Patients in China

Abstract: Background: Much attention has been paid to the quality of life (QOL) in dialysis patients worldwide. However, differences in QOL between peritoneal dialysis (PD) and hemodialysis (HD) patients have not been clearly identified. The objectives of this study were to compare the differences of QOL between PD and HD patients, and to investigate factors contributing to QOL in the Chinese population. Methods: All patients who received PD or HD more than 3 months were enrolled in the study. The demographic and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
(10 reference statements)
2
8
0
2
Order By: Relevance
“…Many studies have explored differences in QoL among patients undergoing Haemodialysis (HD) and Peritoneal Dialysis (PD) (Gokal et al 1999;Avramovic & Stefanovic, 2012;Wu et al 2013) Those patients treated with PD and home HD showed better results than those patients on centre HD (Liem et al 2008;Mau et al 2008). The impairment of QoL of patients with CKD (stage 1-4), not on dialysis, has also recently been evaluated (Perlman et al 2005;Finkelstein et al 2009;Mujais et al 2009).…”
Section: B I O D a T Amentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have explored differences in QoL among patients undergoing Haemodialysis (HD) and Peritoneal Dialysis (PD) (Gokal et al 1999;Avramovic & Stefanovic, 2012;Wu et al 2013) Those patients treated with PD and home HD showed better results than those patients on centre HD (Liem et al 2008;Mau et al 2008). The impairment of QoL of patients with CKD (stage 1-4), not on dialysis, has also recently been evaluated (Perlman et al 2005;Finkelstein et al 2009;Mujais et al 2009).…”
Section: B I O D a T Amentioning
confidence: 99%
“…; Avramovic & Stefanovic, 2012; Wu et al . ) Those patients treated with PD and home HD showed better results than those patients on centre HD (Liem et al . ; Mau et al .…”
Section: Introductionmentioning
confidence: 99%
“…PD patients tended to have lower scores in the role-physical and bodily pain domains whereas HD patients had lower scores in the emotional component [33]. Low quality of life at the initiation of RRT is associated with increased hospitalisation and higher mortality, emphasizing the need for early interventions [34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…Para medirla existe una serie de cuestionarios validados internacionalmente y de amplio uso que han sido aplicados en los estudios recopilados en esta revisión. Los cuestionarios más ampliamente utilizados son el Cuestionario de calidad de vida específico para la enfermedad renal: KDQOL -SF (Tannor, Archer, Kapembwa, van Schalkwyk & Davids, 2017;Wakeel, Harbi, Bayoumi, Al-Suwaida & Ghonaim, 2012;Wright & Wilson, 2015) y sus versiones cortas: SF-36 y SF-12 (Griva et al, 2014;Ikonomou et al, 2015;Iyasere et al, 2016;Oren & Enç, 2013;Ramos, Santos, Zanini, & Ramos, 2015;Wu et al, 2013); y el Cuestionario de calidad de vida de la OMS: WHOQOLBREF (Barata, 2015;Griva et al, 2014;Theofilou, n.d.).…”
Section: Discusión Y Conclusionesunclassified
“…Un gran número de estudios (Ho & Li, 2016;Iyasere et al, 2016;Ramos et al, 2015;Tannor et al, 2017;Wright & Wilson, 2015;Wu et al, 2013), presentan entre sus conclusiones que los pacientes tratados con PD obtuvieron mayor puntuación en gran parte de las escalas de los cuestionarios, pero estos resultados no mostraron una significación estadística concluyente. Hay que tener en cuenta, que los pacientes en PD suelen ser más jóvenes y presentar menos comorbilidades que los pacientes en HD, donde suelen encontrarse pacientes más longevos con una autonomía limitada para llevar el tratamiento domiciliario, además de la mayor independencia y el poder autogestionar el tratamiento (Ho & Li, 2016).…”
Section: Discusión Y Conclusionesunclassified